Analysis of the Relationship Perception of Benefits and Perception of Obstacles to Vaccinate COVID-19 Booster Dosage - Diyah Nur Ekowati; Nurjazuli Nurjazuli; Bagoes Widjanarko (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the relationship between perceived benefits and perceived obstacles to vaccinating booster doses of COVID-19 in Pemalang Regency. This research is quantitative research with a cross-sectional study design. From the results of the hypothesis testing, it was obtained that the p-value of perceived benefits was 0.000, and the P value of perceived obstacles was 0.000. In conclusion, there is a significant relationship between the perception of benefits and intention to vaccinate booster doses of COVID-19 and a meaningful relationship between perceptions of obstacles and choice to vaccinate booster doses of COVID-19. Keywords: Booster, Barriers, Benefits, Intentions, COVID-19 Vaccine